DAMPAK PEMBANGUNAN KAWASAN INDUSTRI CANDI PADA PERILAKU BANJIR KALI SILANDAK KOTA SEMARANG - Setyowati, Dewi Liesnoor; Sugiyanto, R. (Forum Ilmu Sosial, 2013)
There have been land changes in the Watershed of Silandak such as deforestation, changes in land use, and construction of the Candi Industrial Zone. The purpose of the study is: 1) find out the broad development of the industrial area of Candi in 1994-2010, 2) determine the distribution of flood-prone areas of Silandak river, and 3) know the impact of development of Candi Industrial Zone on the flood behavior of Silandak river. The study was conducted at Candi Industrial Zone which is located in the watershed of Silandak river. The analysis technique used are literature studies, ecological approach and descriptive analysis. The distribution of flood-prone areas were analyzed based on the identification of land use maps, land elevation and peak flow discharge. Dominant land use change tend to the direction of settlement and industry. Settlement wide in 1994 amounted to 371.82 hectares, in 2010 increased to 486.35 hectares, and in 1994 the industry total area of 16.10 hectares in 2010 increased to 319.04 hectares. The land use change give impacts on the peak flow discharge increases, from 1.47 m3/second in 1994 increased to 7.23 m3/second in 2010. Flood prone areas that are waterlogged for the longest are located in the Village of Krapyak, Tambakharjo, Jerakah and Tugurejo, while the location of flood prone areas without waterlog are in Tambakaji, Ngaliyan, Bambankerep, Kalipancur, Purwoyoso. The social impact of the development of Candi Industrial Zone is outlined by air quality, noise, land use, the potential for water, waste management, transportation, employment, social unrest, public perception, comfort, and safety.